Floroquinone induces apoptosis and inhibits carcinoma growth in mouse tumor xenograft model of anaplastic thyroid cancer (Bangladesh Journal of Pharmacology, 2016)
In the present study, effects of floroquinone on anaplastic thyroid cancer cell lines and mouse tumor xenografts were investigated. Increase in the concentration of floroquinone from 10 to 100 µM reduced the cell growth from 98 to 17% after 48 hours in HOTHC cells. Similarly, in FRO cells growth rate was found to be 96 and 21%, respectively at 10 and 100 µM concentra-tions of floroquinone. Western blot analysis showed a marked reduction in Bcl-2 expression and increased in Bax, caspase-3 and cleaved PARP expression in HOTHC cell lines on treatment with floroquinone. Floroquinone treatment of the HOTHC cells led to inhibition of the cobalt chloride-induced increase in the hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor expression. In HOTHC cells, floroquinone treatment inhibited the tube formation and migration potential significantly compared to control cells. Treatment of the mouse bearing HOTHC tumor xenograft with 50 and 100 mg/kg doses of floroquinone alternatively for one month reduced the tumor volume to 48 and 17%, respectively compared to the control. Thus, floroquinone effectively inhibits growth of thyroid cancer and can be used for its treatment.Video Clip of Methodology:Migration assay: 1 min 09 sec   Click to watch